2019
DOI: 10.1080/08039488.2018.1554697
|View full text |Cite
|
Sign up to set email alerts
|

Do patients with high-functioning autism have similar social cognitive deficits as patients with a chronic cause of schizophrenia?

Abstract: Do patients with high-functioning autism have similar social cognitive deficits as patients with a chronic cause of schizophrenia?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 43 publications
1
18
0
2
Order By: Relevance
“…Inconsistencies in prior findings have been posited to be due to the utilization of different social cognition tasks across studies (55,58), which also likely measure other aspects of social cognition compared to the task used in our current study. Only two studies have examined social cognition performance in ASD and psychosis using the TASIT, with both finding no significant differences between these clinical groups on TASIT performance consistent with our current findings (54,56).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Inconsistencies in prior findings have been posited to be due to the utilization of different social cognition tasks across studies (55,58), which also likely measure other aspects of social cognition compared to the task used in our current study. Only two studies have examined social cognition performance in ASD and psychosis using the TASIT, with both finding no significant differences between these clinical groups on TASIT performance consistent with our current findings (54,56).…”
Section: Discussionsupporting
confidence: 88%
“…While some studies have similarly found comparable social cognitive abilities in individuals with psychosis and ASD (54-56), others have found a trend towards poorer performance on emotion recognition tasks in individuals with ASD compared to psychosis (55,57). One study found that while there were no group differences in overall social cognition performance between ASD and psychosis, individuals with ASD showed significant deficits only on the social perception task (TASIT) compared to healthy controls, while individuals with psychosis showed deficits on both the social perception task (TASIT) and the ToM task (anthropomorphic animations) compared to healthy controls (54). A meta-analytic review of social cognition in ASD and psychosis concluded that both groups perform poorly on ToM tasks using anthropomorphic animations, but with subtle differences: individuals with ASD performed more poorly than those with psychosis on appropriate descriptions of these animations, whereas individuals with psychosis perform more poorly than those with ASD on ascribing intentions to such animations (58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measures of ever yday functioning were also rare (k = 5). 29,60,[62][63][64] Ten articles 28,30,50,53-57,60,62 reported neuroimaging data in conjunction with performance-based social cognition.…”
Section: Social Cognitive and Additional Measuresmentioning
confidence: 99%
“…There are few empirical data directly comparing both populations to test this hypothesis. This phenomenon is partly due to differences inherent to both disorders that make comparisons between both populations particularly challenging, e.g., differences in prevalence with respect to sex (female-male ratio: 0.92:1 for SSD and 1:4 for ASD, (CDC 2007;Aleman et al 2003;Lugnegard et al 2013), the mean intelligence quotient (IQ) score in representative samples of each disorder (Goldstein et al 2002;Fernandes et al 2018;Veddum et al 2019) and typically different exposure to interventions (such as pharmacotherapy or psychological interventions). In addition, most instruments used to assess social cognition have been developed, and their psychometric properties have been tested in one population or the other.…”
Section: Introductionmentioning
confidence: 99%